2010
DOI: 10.1063/1.3271340
|View full text |Cite
|
Sign up to set email alerts
|

Using Lagrangian coherent structures to analyze fluid mixing by cilia

Abstract: Motivated by the desire to understand the fluid flow within the airway surface liquid of the lung, we consider the flow generated by a computational model of a motile, internally actuated cilium. The cilium, along with a mucus layer modeled by linear elastic elements, is coupled to a viscous, incompressible fluid. The evolution of this coupled system is captured using an immersed boundary method. The Eulerian velocity field computed on a grid is used to compute finite-time Lyapunov exponent fields, whose maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…The possibility of mixing by chaotic advection below the cilia tips is suggested in the experimental studies of Supatto et al (2008) on a single beating cilium in zebrafish embryo and Shields et al (2010) on arrays of artificial cilia beating in synchrony. More concrete evidence of mixing by chaotic advection was reported in the computational studies of Lukens et al (2010) on a single cilium in a two-dimensional fluid and Khatavkar et al (2007) on single and two cilia in a two-dimensional rectangular channel. In the case of two cilia (micro-actuators) beating at a phase difference ∆φ, Khatavkar et al (2007) reported exponential growth in the length of a fluid strip for ∆φ between π/3 and 2π/3 with the optimal value being π/2, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The possibility of mixing by chaotic advection below the cilia tips is suggested in the experimental studies of Supatto et al (2008) on a single beating cilium in zebrafish embryo and Shields et al (2010) on arrays of artificial cilia beating in synchrony. More concrete evidence of mixing by chaotic advection was reported in the computational studies of Lukens et al (2010) on a single cilium in a two-dimensional fluid and Khatavkar et al (2007) on single and two cilia in a two-dimensional rectangular channel. In the case of two cilia (micro-actuators) beating at a phase difference ∆φ, Khatavkar et al (2007) reported exponential growth in the length of a fluid strip for ∆φ between π/3 and 2π/3 with the optimal value being π/2, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 95%
“…At this micro scale, lack of turbulence makes mixing by chaotic advection a nontrivial task (Aref, 1990;Ottino, 1989). The computational results of Lukens et al (2010) showed some evidence of mixing in the flow around a single cilium. A transition from unidirectional flow above the cilium to vortical flow below the cilium was reported by Supatto et al (2008) based on in-vivo experiments that mapped the velocity field surrounding a single beating cilium in zebrafish embryo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the beating frequency of cilia is rather similar between species and organs, and usually varies between 10 and 30 Hz (Supatto and Vermot, 2011). Mathematical models (Lukens et al, 2010) suggest that such a planar motion promotes mixing near the cilia.…”
Section: Directional Cilia-driven Flows: Theory and Modelingmentioning
confidence: 99%
“…For example, it has been recently applied to study flow data in oceans, 15,27 hurricane, 26 flight data, 4,32 gravity wave propagation, 33 some bio-inspired fluid flows, 10,19,21 etc. The idea is to partition the space-time domain into different regions according to a Lagrangian quantity advected along with passive tracers.…”
Section: Introductionmentioning
confidence: 99%